1965
DOI: 10.1126/science.147.3656.400
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Action Spectrum of the Terminal Oxidase of Mixed Function Oxidase Systems

Abstract: The reversal of the carbon monoxide inhibition by bands of monochromatic light was determined for the oxidative demethylation of codeine and monomethyl-4-aminopyrine and the hydroxylation of acetanilide by rat liver microsomes and for the hydroxylation of 17-hydroxyprogesterone at carbon-21 by bovine adrenocortical microsomes. Maximum reversal occurred at 450 millimicrons, the light absorption maximum of the CO compound of the CO-binding pigment of microsomes. The agreement between photochemical action spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2
2

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(104 citation statements)
references
References 9 publications
4
94
2
2
Order By: Relevance
“…Moreover, it was recently shown that the administration of phenobarbital markedly stimulate amount of P-450 and other several lines of evidence indicate that P-450 may have an important role for the oxidation of drugs in liver microsomes (21)(22)(23)(24)(25). Therefore, it was of interest to see whether the alternations in the amount of cytochrome b5 and P-450 by the treatment with phenobarbital or methylcholanthrene in the starved or sucrose fed rats were parallel to these in the activities of drug-metabolizing enzymes and NADPH-dependent electron transfer system.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it was recently shown that the administration of phenobarbital markedly stimulate amount of P-450 and other several lines of evidence indicate that P-450 may have an important role for the oxidation of drugs in liver microsomes (21)(22)(23)(24)(25). Therefore, it was of interest to see whether the alternations in the amount of cytochrome b5 and P-450 by the treatment with phenobarbital or methylcholanthrene in the starved or sucrose fed rats were parallel to these in the activities of drug-metabolizing enzymes and NADPH-dependent electron transfer system.…”
Section: Methodsmentioning
confidence: 99%
“…A role of P450 in steroid hydroxylation was established by D. Cooper et al [14], and the work was carried over to other substrates. A major advance in the study of these mixed-function oxidase reactions occurred in the 1960s with the discovery of a soluble (non-membrane-bound) P450 from the bacterium Pseudomonas putida by I. Gunsalus and co-workers [15].…”
Section: Discovery and Purificationmentioning
confidence: 99%
“…Nonetheless, we considered that pharmacogenomic labeling was not possible at approval for CYP450s and drugs approved before the seminal article of Cooper et al, which was published in 1965. 12 Similarly, for glucose-6-phosphate dehydrogenase, we considered that pharmacogenomic labeling was not present at approval for drugs approved before the publication by Alving and colleagues in 1956. 13 …”
Section: Data Extractionmentioning
confidence: 99%